Cabozantinib (XL184) for the treatment of locally advanced or metastatic progressive medullary thyroid cancer. (August 2013) - Viola, David; Cappagli, Virginia; Elisei, Rossella
Cabozantinib (XL184) is an oral multiple receptor tyrosine kinase inhibitor manufactured by Exelixis Inc., CA, USA. It mainly inhibits three tyrosine kinase receptors: MET, VEGFR2 and RET. In both preclinical and clinical studies it has been shown to inhibit tumor angiogenesis, invasiveness and metastases. The most frequent side effects are fatigue, diarrhea, decreased appetite, nausea, weight loss and palmar–plantar erythrodysesthesia. A Phase III clinical trial (EXAM study) of XL184 versus placebo in advanced and progressive medullary thyroid cancer showed a 28 versus 0% overall response rate and a progression-free survival of 11.2 versus 4.0 months (hazard ratio: 0.28; 95% CI: 0.19–0.40; p < 0.0001) in patients treated with cabozantinib and placebo, respectively. The drug has been approved by the US FDA for the treatment of advanced/progressive metastatic medullary thyroid cancer in the USA. The EMA is now evaluating its approval in Europe.